Implementation of Corporate Governance in Improving Company Performance at ASDP Bakauheni Branch, South Lampung - Putri, Risa Haruman; Masditok, Tokit (Universitas Indonesia Mandiri, 2026)
This study aims to comprehensively analyze the implementation of Good Corporate Governance (GCG) at PT ASDP Indonesia Ferry (Persero), Bakauheni Branch, South Lampung. The research examines the governance structure, oversight mechanisms, application of GCG principles, work ethics, risk management, and the branch’s compliance with head office policies. Recent revisions and developments also include an in-depth analysis of post-flood conditions in the South Lampung region, particularly how the flooding affected operational stability and the extent to which GCG implementation experienced changes The results indicate that although the organizational structure at the branch level is not as complete as that of the head office, GCG implementation remains effective due to the use of digital reporting systems and multilayered supervision. In the post-flood period, the implementation of GCG was found to have improved, especially in terms of transparency, accountability, and social responsibility. The Bakauheni Branch of ASDP also carried out a series of social initiatives, including the distribution of logistics and emergency assistance to communities affected by the flooding.